Identification of a novel point mutation in gene in a patient with adrenal hypoplasia congenita - Han Saem Choi; Ahreum Kwon; Hyun Wook Chae; Junghwan Suh; Kyung Chul Song; Jin-Sung Lee; Ho-Seong Kim (Korean Society of Pediatric Endocrinology, 2021)
X-linked adrenal hypoplasia congenita caused by a mutation in NR0B1/DAX-1 is a rare inherited disorder. Patients with adrenal hypoplasia congenita are usually diagnosed with primary adrenal insufficiency in infancy or early childhood and present hypogonadotropic hypogonadism during adolescence. Our patient first presented with adrenal crisis at the age of 2 months, which was managed with glucocorticoids and mineralocorticoids. At the age of 17 years, testicular volumes of 5 mL each and a stretched penile length of 4 cm were noted. A combined pituitary function test showed a peak luteinizing hormone level of 2.68 mIU/mL, testosterone 13.5 ng/dL, confirming hypogonadotropic hypogonadism. After whole-exome sequencing, a new variant of DAX-1, c.881T>C (p.Leu294Pro), was found. He was diagnosed with X-linked adrenal hypoplasia congenita and then treated with human choriogonadotropin for the induction of spermatogenesis as well as with steroid replacement therapy.